PREDIKSI AIR LIMBAH DOMESTIK (KELOLA SWADAYA MASYARAKAT HIDUP SEHAT) IPAL KOMUNAL DESA KEBON AYU KECAMATAN GERUNG KABUPATEN LOMBOK BARAT - YOHANES JAKA MERE; BAGUS WIDHI DHARMA S.; BAIQ RENI SARI DEWI (LPPM PSDKU Kampus Mataram UNMAS Denpasar, 2021)
The purpose of this study was to determine the capacity of the Communal WWTP in Kebon Ayu Village, Gerung District, and describe the Communal WWTP Wastewater storage in Gerung District. The processing process used for the Kebon Ayu Village complex is a deposition process, a biological process, a chemical process and an advanced process. The distribution system used is a separate distribution system where the wastewater discharge is separated from the rainwater discharge. The results showed that the wastewater treatment plant of the Kebon Ayu Village Complex produces 100% of waste water from the use of clean water, which is 231.82 liters of people per day. While the estimated population growth over the next 5 years is 6,646 starting from 2016 (2476 people) - 2020 (6,720 people)